SUPERLIQUIDUS DIFFERENTIATION OF FLUID-BEARING MAGMATIC MELTS UNDER REDUCING CONDITIONS AS A POSSIBLE MECHANISM OF FORMATION OF LAYERED MASSIFS: EXPERIMENTAL INVESTIGATIONS - Bezmen N.I. (My University, 2001)
Previous experimental work (Bezmen, 1992; Bezmen and Elevich, 1998) demonstrated that, at certain critical thermodynamic parameters (temperature, pressure, and fluid phase composition), melts become unstable and show cryptic or contrast layering. Layering in ultrabasic melts, separation from silicate melts of ore liquids enriched in chromite, ilmenite, and apatite were obtained under superliquidus conditions at H-O-C-S fluid pressure. The proportions of gases in the fluid phase were specified to provide the closest approach to the compositions of natural fluids. At constant thermodynamic parameters and the absence of temperature gradient, fluid-bearing melts exhibit liquid-state layering, which develops gravitationally on a macromolecular scale. An increase in the duration of experiments results in a stronger contrast and appearance of layers with new compositions. The transmission electron microscopic investigation of quench glasses revealed ellipsoid-shaped inclusions with a crystalline structure and diffuse outlines, 6 nm (60 Å) and more in size. It is supposed that these are cores of clusters, which occur in strongly depolymerized fluid melts. The formation of clusters is a consequence of the fluctuation quasi-crystalline structure of magmatic melts. According to modern data obtained in situ (Cohen and Knight, 1990), clusters are a transitional state of matter between liquid and crystal. The cluster is composed of an ordered core and a shell consisting of ligands (Tredoux et al., 1995). The latter provide cluster stability in time. Atoms in the ligand shell are more mobile and the structure as a whole is a pseudocrystalline core with a liquid-like surface. High-pressure experiments demonstrated that the presence of a fluid phase similar in composition to natural magmatic fluid provides necessary conditions for the gravitational movement of clusters and their aggregates. The liquid-state cluster differentiation of melts allows us to explain a number of issues in the evolution of differentiated complexes including the nature of cryptic layering, rhythmic structure of layered sections, selective concentration of ore components by melts, development of fine-grained and homogranular textures, concentration of dense minerals in the upper portions of massif sections, formation of monomineral rocks and massive ores, and others.